Pneumococcal VncR Strain-Specifically Regulates Capsule Polysaccharide Synthesis - Ghosh, Prachetash; Shah, Masaud; Ravichandran, Subramaniyam; Park, Sang-Sang; Iqbal, Hamid; Choi, Sangdun; Kim, Kyeong Kyu; Rhee, Dong Kwon (Frontiers in Microbiology, 2019)
Capsular polysaccharides (CPS), a major virulence factor in Streptococcus pneumoniae, becomes thickened during blood invasion than during asymptomatic nasopharyngeal colonization. However, the underlying mechanism controlling this differential pneumococcal CPS regulation remains unclear. Here, we show how VncR, the response regulator of the vancomycin resistance locus (vncRS operon), regulates CPS expression in vncR mutants in three serotype (type 2, 3, and 6B) backgrounds upon exposure to serum lactoferrin (LF). Comparative analysis of CPS levels in the wild type (WT) of three serotypes and their isogenic vncR mutants after LF exposure revealed a serotype-specific alteration in CPS production. Consistently, VncR-mediated serotype-specific CPS production is correlated with pneumococcal virulence, in vivo. Electrophoretic mobility-shift assay (EMSA) and co-immunoprecipitation (co-IP) revealed an interaction between VncR and the cps promoter (cpsp) in the presence of serum. In addition, in silico analysis uncovered this protein-DNA interaction, suggesting that VncR binds with the cpsp, and recognizes the serotype-specific significance of the tandem repeats in cpsp. Taken together, the interaction of VncR and cpsp after serum exposure plays an essential role in regulating differential serotype-specific CPS production, which subsequently determines serotype-specific systemic virulence. This study highlights host protein LF contributes in pneumococcal VncR-mediated CPS production. As CPS plays significant role in immune evasion, these findings propose that drug designed to interrupt the VncR-mediated CPS production could help to alleviate pneumococcal infection.